Ecological bag as a touristic product bolsa ecológica - González González, Sindy Odaly (2024)
The following work is born with the idea to make a change in the community through the elaboration of a touristic product. It comes from embracing one challenge after another and coming up with the idea to make the world a better place, even in small ways. Thus, my pulgarcito bag, an ecological bag made of cotton called “manta cruda” is born from the necessity of supporting the environment, and setting up my own business, better yet being a job generator as long as the business is growing up. The report is divided into five chapters which describe how this touristic product has been elaborated. To begin with the description and characteristics of the products, as well the mission and vision of the company as a guide. Then we move on the conditioning elements of the product where tourism history is part of the process, entrepreneur characteristics, barriers and success factors. In chapter three, the responsibility as entrepreneur will be studied, laws that support the product and the quality norms too. Finally, the logo, a costing plan, mission and vision which have been decided and established for the company will be showing up. Therefore, having set up a business plan goes beyond to sell a product or service, history is also part of it, besides all characteristics an entrepreneur must fill up and the bravery to face any challenge along the journey.